[PP.12.09] MASKED-UNCONTROLLED HYPERTENSION MANAGEMENT BASED ON OFFICE BP OR ON OUT-OF-OFFICE (AMBULATORY) BP MEASUREMENT (MASTER): STUDY PROTOCOL. (September 2017) - Parati, G.; Rosei, E. Agabiti; Bakris, G.; Bilo, G.; Branzi, G.; Faria, T.; Mancia, G.; McManus, R.; Modesti, P.; Ochoa, J.; Omboni, S.; Pellegrini, D.; et al.
Abstract : Objective: Masked uncontrolled hypertension (MUCH) carries an increased risk of cardiovascular (CV) complications and can be identified through combined use of office (O) and ambulatory (A) blood pressure (BP) monitoring (M) in treated patients. It is not clear yet whether this condition represents a target for treatment. A randomized intervention study comparing management of MUCH based on OBPM or on ABPM could help clarifying this issue, and would at the same time provide a perfect setting to assess the actual clinical role of ABPM. MASTER study will compare the effects of a management strategy of MUCH based on ABPM vs OBPM on CV and renal intermediate outcomes at one year; on CV events at 4 years and on changes in BP–related variables throughout the study Figure. No caption available. Design and method: MASTER study is a 4-year prospective, randomized, open-label, blinded-endpoint investigation. A total of 1240 treated hypertensive patients from about 40 clinical centers worldwide will be included upon confirming the presence of MUCH (repeated OBP < 140/90 mmHg, and at least one of the following: daytimeABP > 135/85 mmHg; night-timeABP > 120/70 mmHg; 24 hABP > 130/80 mmHg). Patients will be randomized to a management strategy based on OBPM(Group1) or ABPM (Group2). Patients in Group1 will have OBPM at 0, 3, 6, 12, 18, 24, 30, 36, 42, 48 months; ABPM will only be performed at randomization and at 12, 24, 36, 48 months but will not be used to take treatment decisions. Patients randomized to Group2 will have ABPM performed at randomization and at all scheduled visits, and antihypertensive treatment will be adjusted whenever ABP exceeds normal values (Figure) Results: MASTER will evaluate whether an ABPM-based strategy is superior to an OBP-based strategy in changing LVmass and microalbuminuria (intermediate co-primary-outcome) and in preventing CV events (secondary outcome). Conclusions: Although the superiority of ABPM over OBP has been repeatedly shown by observational studies, key evidence from randomized intervention trials on the actual clinical value of ABPM is still missing. The results of the MASTER study will help to clarify whether an ABPM-guided treatment strategy provides a greater benefit in terms of prevention/regression of organ damage and reduction in CV events than a strategy based on conventional OBP measurements